(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Tinea versicolor is a superficial fungal infection caused by Malassezia species characterised by asymptomatic, scaly, hyperpigmented (chromic), hypopigmented (achromic), or erythematous macules and patches involving the seborrheic areas (trunk, neck, and/or arms). An atypical clinical form of pityriasis versicolor has been infrequently reported, in which cutaneous atrophy is associated with individual pityriasis versicolor lesions.A 39-year-old female patient presented with multiple, slightly scaly, hyperpigmented depressed patches on the left side of the arm, abdomen, thigh and leg. Our microscopic examination of the skin scrapings on a KOH preparation revealed numerous short hyphae and spores. We report this case of atrophying tinea versicolor because of its rarity,unilateral and non seborrheic area involvement which is easily misdiagnosed.